İskeletsel Sınıf II Hastada Stöckli-Teuscher Tedavisi: Olgu Sunumu - TURAN, BEGÜM; ÖNEM ÖZBİLEN, ELVAN (My University, 2022)
Amaç: Bu vaka raporunun amacı, iskeletsel Sınıf II hastanın Stöckli-Teuscher (Headgear destekli Bionator) apareyi ile fonksiyonel ve ortodontik tedavisini sunmaktır.Birey ve Yöntem: Kronolojik yaşı 10 yıl 8 ay olan erkek hasta üst çenesinin önde olması şikayeti ile kliniğimize başvurmuştur. Hastanın intraoral muayenesinde 11,9 mm overjet, 6,2 mm overbite ve Sınıf II dental ilişki olduğu görülmüştür. Ekstraoral muayenede ise hasta simetrik yüz, konveks profil ve dudak yetersizliğine sahiptir. Sefalometrik değerlendirmede; mandibuler gelişim yetersizliğine bağlı iskeletsel Sınıf II ilişki (SNA: 82°, SNB: 77°, ANB:5°), artmış üst keser açıları (U1-SN: 120°) ve artmış alt keser açısı (IMPA: 96°) tespit edilmiştir. Tedavi planlamasında, iskeletsel Sınıf II ilişkiyi düzeltmek ve iyi bir estetik sağlayabilmek için Stöckli-Teuscher apareyi takiben sabit ortodontik tedaviye geçilmesine karar verilmiştir. Stöckli-Teuscher apareyi 13 ay süreyle kullandırılmıştır. Hastanın tedavi süresi sabit tedavi ile birlikte toplam 28 ay sürmüştür. Retansiyon için lingual pekiştirme teli kullanılmıştır.Bulgular: Tedavi sonrası SNA açısı 79°’ye, ANB açısı 2°’ye düşmüştür. Hastanın üst keser açıları azalmış (U1-SN: 112°), alt keser açısında ise artış meydana gelmiştir (IMPA: 106°). Tedavi sonunda ideal overjet ve overbite ilişkisi elde edilmiştir.Sonuç: Büyüme gelişimi devam eden iskeletsel Sınıf II hastalarda fonksiyonel aparey tedavisi iyi bir tedavi seçeneğidir. İyi bir kooperasyona sahip hastanın profilinde de Stöckli-Teuscher apareyi ile olumlu değişiklikler elde edilmiştir.Anahtar Kelimeler: Ekstraoral aparey, Fonksiyonel Tedavi,Sınıf II Malokluzyon

Objective: The aim of this case report is to present the functional and orthodontic treatment of a skeletal Class II patient with the Stöckli-Teuscher (Headgear supported Bionator) appliance.Case: A male patient with a chronological age of 10 years and 8 months applied to our clinic with the complaint of anteriorly positioned maxilla. Intraoral examination of the patient revealed an overjet of 11.9 mm, an overbite of 6.2 mm and a Class II dental relationship. At extraoral examination, the patient has a symmetrical face, convex profile, and lip deficiency. In cephalometric evaluation; Skeletal Class II relationship (SNA: 82°, SNB: 77°, ANB: 5°), increased upper incisor angles (U1- SN: 120°) and increased lower incisor angle (IMPA: 96°) due to mandibular deficiency were detected. In the treatment planning, it was decided to continiue to fixed orthodontic treatment following the Stöckli-Teuscher appliance in order to correct the skeletal Class II relationship and provide a good aesthetic. The Stöckli-Teuscher appliance was used for 13 months. The duration of the patient’s treatment lasted for a total of 28 months with fixed treatment. A lingual retainer wire was used for retention.Results: After the treatment, the SNA angle decreased to 79° and the ANB angle to 2°. The patient’s upper incisor angle decreased (U1-SN: 112°), while the lower incisor angle increased (IMPA: 106°). At the end of the treatment, the ideal overjet and overbite was obtained.Conclusion: Functional appliance therapy is a good treatment option in skeletal Class II patients with continued growth. Positive changes were obtained with the Stöckli-Teuscher appliance in the profile of the patient with good cooperation.Keywords: Class II malocclusion, Extraoral appliances, Functional Treatment
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)